Place of Drunkenness or Space of Gastronomy Culture? Communication of Catering Institutions in Interwar Lithuanian Magazine Moteris - Laužikas, Rimvydas (Lietuvos istorijos studijos, 2025)
In the late 19th and early 20th centuries, in the creation of the Lithuanian nationalidentity, ethnolinguistic ‘Lithuanianness’ performed a key role, and its core constituents wererelated with the agricultural culture of Lithuanian-speaking peasants/farmers. The roots ofthis identity date back to the Enlightenment and Romanticism movements, when the ideaof the ‘noble savage’ was being promoted, which elevated humans who were not spoiled bycivilization, yet living in the vicinity of nature and leading a lifestyle based on the rhythm of nature. These ideas served as the background for an opposition between Lithuanian identityand the tavern/inn (in all of its manifestations, involving such catering institutions as the caféand the restaurant). Impact on the development of opposition between the Lithuanian andthe inn was also made by the historic reality of the proliferation of inns and the temperance(i.e., sobriety) movement initiated by Bishop Motiejus Valančius.The article explores the communication of the inn, tavern, café, restaurant and teahousein the interwar Lithuanian magazine Moteris (The Woman). It has been established thatnegative narratives were predominant, which related catering institutions with alcoholabuse, immoral lifestyle, prostitution, wasting time and money, horrible manners, lackof education and absence of religious feelings. Attending a catering institution was presentedprimarily as a feature that could be observed in men, which was inappropriatefor a woman, and extremely harmful to young women/girls. In this negative context, thedifference between specific types of catering institutions (a tavern, an inn, a beer house,a café, a restaurant) in terms of their interpretation is minor. Intense modernization ofthe gastronomy culture, which took place in interwar Lithuania, had only a minor impacton changes in the negative image of catering institutions.
Keywords: inn/tavern; catering establishment; alcohol abuse; magazine Moteris; Lithuania in 1918–1940